Rancangan Sistem Informasi Penjualan Pada Toko Aditya Jaya Bata - Putri Salsabila; Amanda Amanda; Ambar Fhadila; Fika Yova; Sri Murni (Jurnal Sistem Informasi Akuntansi, 2025)
This study aims to analyze the sales accounting information system at the Aditya Jaya Bata Shop. Through observations, interviews, and literature studies, researchers identify the need for a more structured and digital approach. This study uses the Waterfall method in designing a prototype system using Figma, supported by UML modeling devices such as Use Case, Activity, and Sequence Diagrams. The proposed system provides an easy -to -use interface to record, manage, and monitor payments at the Batako Shop. With the application of the interface design that is built in the future it is expected that this prototype can be used to support online buying and selling transactions